PENGEMBANGAN KURIKULUM KEWIRAUSAHAAN - Mei Ie; Hetty Karunia Tunjungsari (PROSIDING SERINA, 2021)
Entrepreneurship education can be integrated into existing curricula in schools. Entrepreneurship curriculum development can be implemented in educational activities. Responding to the importance of knowledge and mastery of entrepreneurship, the Principal of Al-Jannah Islamic High School, Nature, and Science School submitted a request to the Untar community seerevice Team to be able to help develop an entrepreneurship curriculum for students at the school. The school has a great concern for developing an entrepreneurial spirit in its students and equipping students with adequate knowledge so that they can run their business better and become successful entrepreneurs in the future. The solution to the problems faced by partners is through the provision of mentoring activities for the preparation of the entrepreneurship curriculum. The output target that will be produced from this community service is in the form of knowledge transfer regarding the preparation of an entrepreneurship curriculum that can be applied at Al-Jannah Islamic High School, Nature, and Science School. In addition, this community service activity is also expected to be able to develop the interest of Al-Jannah Islamic, Nature, and Science School students towards the entrepreneurial profession as one of the professional choices in the future. Mandatory output targets which will also be produced by the proceedings of scientific meetings (seminars on community service activities) organized by Tarumanagara University. The method of implementing the activities is conducting in-depth interviews, studying relevant literature, compiling a plan for mentoring activities, implementing community service activities, evaluating activities, as well as preparing and submitting activity reports.